2015
DOI: 10.1002/2014jg002878
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent groundwater contributions influence patterns of winter baseflow stream chemistry in boreal catchments

Abstract: Understanding how the sources of surface water change along river networks is an important challenge, with implications for soil-stream interactions, and our ability to predict hydrological and biogeochemical responses to environmental change. Network-scale patterns of stream water reflect distinct hydrological processes among headwater units, as well as variable contributions from deeper groundwater stores, which may vary nonlinearly with drainage basin size. Here we explore the spatial variability of groundw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 66 publications
2
92
0
Order By: Relevance
“…The temperature dependence (and activation energy) of biotic reactions increases with greater molecular complexity (Davidson and Janssens ), and DOC in boreal streams is generally humic with a high‐molecular weight (Thurman ). Moreover, a reduction in the supply of freshly leached C resources may also occur during winter, when soil frost isolates riparian and upland hydrological pathways and the relative contribution of deep, older groundwater increases (Ågren et al ; Peralta‐Tapia et al ). Reduced insolation for ice‐covered streams may also eliminate the production of labile C from both photochemical degradation (Köhler et al ) and exudation from aquatic autotrophs (e.g., Baines and Pace ) during winter months.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature dependence (and activation energy) of biotic reactions increases with greater molecular complexity (Davidson and Janssens ), and DOC in boreal streams is generally humic with a high‐molecular weight (Thurman ). Moreover, a reduction in the supply of freshly leached C resources may also occur during winter, when soil frost isolates riparian and upland hydrological pathways and the relative contribution of deep, older groundwater increases (Ågren et al ; Peralta‐Tapia et al ). Reduced insolation for ice‐covered streams may also eliminate the production of labile C from both photochemical degradation (Köhler et al ) and exudation from aquatic autotrophs (e.g., Baines and Pace ) during winter months.…”
Section: Discussionmentioning
confidence: 99%
“…A prerequisite for this is that pH increases with increasing catchment area, while the TOC concentration decreases, which causes both Fe and Al to precipitate (Köh-ler et al, 2014;Lidman et al, 2014). This is in turn related to less organic matter in the riparian soils of larger streams and an increasing influence from deeper groundwater, which entirely may bypass the riparian soils (Peralta-Tapia et al, 2015;Lidman et al, 2016).…”
Section: Soil Water and Groundwater Chemistrymentioning
confidence: 99%
“…For example, Karlsen et al () showed that for subcatchments of the Krycklan basin in Sweden, specific discharge during the summer low‐flow period increased with catchment area and with the fraction of area characterized by deeper sediment deposits, but summer low flows were smaller in catchments with denser forest cover. Also, at Krycklan, Peralta‐Tapia et al () reported increasing contributions from deeper groundwater sources with increasing catchment area during winter baseflow. Similar increases in groundwater contributions with increasing catchment area during baseflow were observed in a forested catchment in Japan by Egusa, Ohte, Oda, and Suzuki () and in the southern Rocky Mountains by Frisbee, Phillips, Campbell, Liu, and Sanchez ().…”
Section: Introductionmentioning
confidence: 95%